A case of appendiceal mucinous cystadenoma which presented as painless purulent umbilical discharge. Issue 8 (22nd August 2019) - Al Buainain, Latifa; Al Khaldi, Turki; Tahseen, Wael Mohamed
Abstract : A 57-year-old obese, diabetic woman, presented with 1 day history of purulent umbilical discharge. She was vitally stable and afebrile. Abdominal examination revealed a full abdomen with purulent discharge from the umbilicus, swelling with erythema and induration surrounding the umbilicus. Lab tests were normal. Initial impression was abdominal wall abscess. Ultrasound showed subcutaneous fluid collection. Non-contrast CT showed collection and abdominal wall defect at the umbilicus. On exploration of the abscess cavity, there were two defects (umbilical and supraumbilical) with appendix protruding through the umbilical defect and a part of a small bowel and omentum adherent to the other defect. Wash was given, bowel and omentum were released and appendectomy was performed. Histopathology showed mucinous cystadenoma with periappendicitis. We would like to highlight the rare occurrence of an appendiceal mucinous cystadenoma in such a clinical presentation.